2014
DOI: 10.1038/nsmb.2846
|View full text |Cite
|
Sign up to set email alerts
|

Molecular basis for unidirectional scaffold switching of human Plk4 in centriole biogenesis

Abstract: Polo-like kinase 4 (Plk4) is a key regulator of centriole duplication, an event critical for the maintenance of genomic integrity. Here we showed that Plk4 relocalizes from the inner Cep192 ring to the outer Cep152 ring as newly recruited Cep152 assembles around the Cep192-encircled daughter centriole. Crystal structure analyses revealed that Cep192 - and Cep152-derived peptides bind the cryptic polo box (CPB) of Plk4 in opposite orientations and in a mutually exclusive manner. The Cep152-peptide bound to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
164
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 96 publications
(177 citation statements)
references
References 41 publications
13
164
0
Order By: Relevance
“…In dividing cells, Asl serves as a receptor recruiting Plk4 to the centriole for centriole duplication [24, 27, 30, 31]. However, Asl’s interaction with Plk4 is complex and mediated via two distinct domains (Asl C-terminus and N-terminus), which have distinct functions during centriole duplication [22].…”
Section: Resultsmentioning
confidence: 99%
“…In dividing cells, Asl serves as a receptor recruiting Plk4 to the centriole for centriole duplication [24, 27, 30, 31]. However, Asl’s interaction with Plk4 is complex and mediated via two distinct domains (Asl C-terminus and N-terminus), which have distinct functions during centriole duplication [22].…”
Section: Resultsmentioning
confidence: 99%
“…In mammalian cells, CEP295 directly binds to CEP192 and contributes to the stabilization of centrioles after the loss of the cartwheel upon mitotic exit 89,94 . Considering that CEP152 and CEP192 form scaffolds for the recruitment of PLK4 9599 , the kinase essential for centriole duplication (see below), these results explain why post-mitotic PCM assembly is required to confer duplication competence to procentrioles 91 . While C.elegans lack an obvious CEP295/Ana1 homolog, recent work has shown that the SAS-7 protein interacts with SPD-2 and is required for procentrioles to acquire competence to duplicate, suggesting SAS-7 may function analogously to CEP295 100 .…”
Section: Control Of Centriole Numbermentioning
confidence: 92%
“…In mammalian cells, PLK4 is recruited to centrioles through binding to two distinct scaffolding proteins, CEP152 and CEP192 9599 . Super-resolution microscopy shows that both CEP152 and CEP192 form rings around parent centrioles and, accordingly, PLK4 can also be seen to form rings in G1 phase.…”
Section: Control Of Centriole Numbermentioning
confidence: 99%
“…Two polo‐like kinases (PLKs), PLK4 and PLK1, play crucial roles in centriole duplication and microtubule nucleation (20). PLK4 interacts with Cep192 and then switches to Cep152 in the subsequent centriole replication cycle (19, 21). Chemical inhibition of PLK4 kinase activity reversibly depletes the centrioles in somatic cells (22), suggesting the importance of PLK4 in centriole duplication.…”
mentioning
confidence: 99%